Post-COVID-19 headache- NDPH phenotype: a systematic review of case reports - Dhiman, Neetu Rani; Joshi, Deepika; Singh, Royana; Gyanpuri, vyom; Kumar, Anand (Frontiers in Pain Research, 2024)
Background and objectives: Post-acute COVID-19 syndrome or 'long COVID' affects patients even after the recovery from Covid infection in various ways. Persistent headache or New Daily Persistent Headache (NDPH) is one of such symptoms. In this review, we will discuss about the case-reports of post covid-19 headache-NDPH phenotype both after and in the course of COVID-19 infection.Case reports/studies talked about patients having NDPH around the disease either immediately or late post COVID were included. Data was taken from the source and synthesised on a qualitative basis.Results: Literature search showed 3538 articles, out of which 12 were screened as per the eligibility criteria and finally, 4 case reports on NDPH and Covid-19 were chosen for analysis from the database and by human search. All case reports justify the criteria for acceptability in quality for this systematic review.Covid 19 infection is something that is currently an ingenious debated topic in the scientific community. More case studies should be written and published on the same subject so that a large systematic review could be conducted.The review is registered in Prospero with no.